2007
DOI: 10.1159/000110454
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Precursors Display Dynamic Metabolic Shifts toward Accelerated Glucose Metabolism at an Early Stage of RANKL-Stimulated Osteoclast Differentiation

Abstract: Mature osteoclasts have an increased citric acid cycle and mitochondrial respiration to generate high ATP production and ultimately lead to bone resorption. However, changes in metabolic pathways during osteoclast differentiation have not been fully illustrated. We report that glycolysis and oxidative phosphorylation characterized by glucose and oxygen consumption as well as lactate production were increased during receptor activator of nuclear factor-ĸB ligand (RANKL)-induced osteoclastogenesis from RAW264.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 32 publications
8
120
1
3
Order By: Relevance
“…We did not observe altered osteoclast functions ex vivo, in contrast to other reports, which suggested that a diabetic microenvironment tends to inhibit osteoclast differentiation and function (30,16,29,4,12). However, none of these studies used an in vivo model of rats with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not observe altered osteoclast functions ex vivo, in contrast to other reports, which suggested that a diabetic microenvironment tends to inhibit osteoclast differentiation and function (30,16,29,4,12). However, none of these studies used an in vivo model of rats with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
“…It could also be an indication for the skeleton to instigate the appropriate bone remodeling response associated either with augmentation of energy-producing processes or decreased energycosting processes. Changes in metabolic pathways indeed occur during bone cell differentiation and function to allow high ATP generation for bone matrix production and mineralization, as well as for bone resorption (Komarova et al 2000, Kim et al 2007. The potential role of AMPK in the regulation of bone homeostasis is shown in Fig.…”
Section: Ampk and The Relationship Between Bone And Fatmentioning
confidence: 99%
“…For example, glycolysis, a metabolic pathway, occurs in the monocytic cytosol, giving rise to adenosine triphosphate (ATP) as one of the main energy sources for cellular differentiation and migration [15]. Cytosolic proteins for biosynthetic substrates and metabolic enzymes for energy generation are increasingly expressed during the receptor activator of nuclear factor kappa-B ligand (RANKL)-stimulated osteoclastogenesis [16]. Importantly, proteins in monocytes may have specific functional roles depending on distinct subcellular localizations.…”
Section: Introductionmentioning
confidence: 99%